2009
DOI: 10.1146/annurev.publhealth.031308.100243
|View full text |Cite
|
Sign up to set email alerts
|

Quality-Based Financial Incentives in Health Care: Can We Improve Quality by Paying for It?

Abstract: This article asks whether financial incentives can improve the quality of health care. A conceptual framework drawn from microeconomics, agency theory, behavioral economics, and cognitive psychology motivates a set of propositions about incentive effects on clinical quality. These propositions are evaluated through a synthesis of extant peerreviewed empirical evidence. Comprehensive financial incentivesbalancing rewards and penalties; blending structure, process, and outcome measures; emphasizing continuous, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
138
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 77 publications
0
138
0
Order By: Relevance
“…In addition, government legislation disallowing Medicare (2008) and Medicaid (2012) reimbursement for low-quality care (eg, the costs associated with hospital-acquired CLABSI) is intended to support the high-value objective. Although several studies have found little impact of nonpayment on quality improvement, 13,14 the use of nonpayment as a policy tool to deter low quality suggests that the excess costs associated with the occurrence of a provider-induced injury or illness are sufficiently high to provide incentives against HAI.…”
mentioning
confidence: 99%
“…In addition, government legislation disallowing Medicare (2008) and Medicaid (2012) reimbursement for low-quality care (eg, the costs associated with hospital-acquired CLABSI) is intended to support the high-value objective. Although several studies have found little impact of nonpayment on quality improvement, 13,14 the use of nonpayment as a policy tool to deter low quality suggests that the excess costs associated with the occurrence of a provider-induced injury or illness are sufficiently high to provide incentives against HAI.…”
mentioning
confidence: 99%
“…Moreover, physicians' lack of responsiveness may be due to payments that are too small (Conrad and Perry, 2009). In a comprehensive survey, Christianson, Sutherland and Leatherman (2009) conclude that studies with stronger research design report no impacts of financial incentives on quality and so the evidence for justifying the growing use of pay-for-performance schemes is thin and inconclusive.…”
Section: The Role Of Financial Incentives For Health Care Improvementsmentioning
confidence: 99%
“…1,6,9,10 Other arguments supporting team-level incentives include the greater reliability of quality measurement at the group level compared with the individual level, the increasing amount of health care provided by teams rather Jessica Greene, PhD than individuals, the belief that team incentives will better maintain clinicians' intrinsic motivation for providing high-quality care, and that team incentives will bring about greater cooperation among team members. 9,[11][12][13] Several authors, however, have expressed concern that team-based incentives may result in clinicians getting a free ride on their colleagues' work. 1,9,14 Recommendations for using individual-level incentives often focus on trying to change behaviors that are under a clinician's control, such as counseling patients on smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…9,[11][12][13] Several authors, however, have expressed concern that team-based incentives may result in clinicians getting a free ride on their colleagues' work. 1,9,14 Recommendations for using individual-level incentives often focus on trying to change behaviors that are under a clinician's control, such as counseling patients on smoking cessation. 6, 15 Mehrotra and colleagues have also argued that individual-level incentives are important for sparking clinician-level quality improvement.…”
Section: Introductionmentioning
confidence: 99%